Entropy-synergistic introduction as comprehensive research basis of complex objects state - Kozulia, T.V.; Kozulia, M.M. (Вопросы атомной науки и техники, 2020)
The article deals with information support formation problem for comprehensive state assessment definition of research various nature object as a result of establishing compliance with safety requirements. The factors state stabilization analysis methods system and stationary communication of the “environment – object” is proposed. On information-entropy changes assessment basis by results of cognitive analysis of graphological models of system objects, cause-effect relationships are established for the in uence manifestation between systems within object boundaries, external environment on object as a whole. Synergetics elements use for the essential mechanisms allocation in organizing order for selective instability and the regulation or arbitrary processes consolidation synchronization probabilistic manifestation in the interaction “environment – object” is proposed.